Perbandingan Harga Pokok Produksi Keripik Pisang Pada Agroindustri Skala Kecil dan Skala Mikro di Kota Jambi - Maulida Putri Maharani; Gina Fauzia; Ernawati Hamid (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
Due to the rise of similar enterprises, the processing of banana chips is becoming more and more competitive. The most crucial factor in determining an agroindustry's costs and, consequently, its optimal selling price is the cost of production. For the agroindustry to potentially set a good selling price without forgetting the production costs incurred, determining the cost of production using the complete costing approach presents all costs that are not used as production costs but should be part of the production costs. The study examines the costs of producing banana chips on a small- and micro-scale in the agricultural sector. The two agricultural industries that were chosen are the small-scale Darma Jaya and the micro-scale Virgi. These industries differ in terms of business scale. This data underwent quantitative descriptive analysis. The entire costing computations are used in the data analysis procedure. According to the study's findings, the cost of producing a 100-gram product of banana chips in small-scale agriculture (Darma Jaya) is IDR 5,703.94, while in micro-agriculture (Virgi), it is IDR 7,982.73. The cost of production for a 100-gram product at Agroindustry Darma Jaya was IDR 6,372.72, while for Agroindysri Virgi, it was IDR 8,548.74, according to the whole costing technique calculation. Cost accounting calculations should be used by the agroindustry to determine that the selling price set should be higher than the cost of production to optimize profits. The agro-industry does not include many costs when determining production costs. Hence, the cost of production is not determined using the full costing approach.